2018
DOI: 10.3233/jad-170909
|View full text |Cite
|
Sign up to set email alerts
|

A Network of Genetic Effects on Non-Demented Cognitive Aging: Alzheimer’s Genetic Risk (CLU + CR1 + PICALM) Intensifies Cognitive Aging Genetic Risk (COMT + BDNF) Selectively for APOE ɛ4 Carriers

Abstract: Background Trajectories of complex neurocognitive phenotypes in preclinical aging may be produced differentially through selective and interactive combinations of genetic risk. Objective We organize three possible combinations into a “network” of genetic risk indices derived from polymorphisms associated with normal and impaired cognitive aging, as well as Alzheimer’s disease (AD). Specifically, we assemble and examine three genetic clusters relevant to non-demented cognitive trajectories: (1) Apolipoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 82 publications
2
25
0
Order By: Relevance
“…was not certified by peer review) (which The copyright holder for this preprint this version posted October 10, 2019. . https://doi.org/10.1101/19008615 doi: medRxiv preprint prediction of cognitive trajectories and clinical outcomes have also been reported (Sapkota and Dixon, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…was not certified by peer review) (which The copyright holder for this preprint this version posted October 10, 2019. . https://doi.org/10.1101/19008615 doi: medRxiv preprint prediction of cognitive trajectories and clinical outcomes have also been reported (Sapkota and Dixon, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies were in healthy older adults, although two studies included participants with established AD/MCI [11,26], two studies had young adult participants [51,57], one study had adolescent participants [40] and one included longitudinal data from children aged 11 [59]. There were some cross-sectional studies that only reported associations with AD polygenic risk and cognition at one timepoint [40, 50-52, 54, 55, 57, 68], whereas longitudinal studies were able to report the correlations with change in cognition over time [11,26,31,33,36,44,45,56,60,[62][63][64]. As expected, most studies reported that the effects attenuated or were no longer significant when APOE was excluded from the PRS.…”
Section: Cognitive Measuresmentioning
confidence: 99%
“…Of these, cognition has been the most widely investigated. While the methodology and samples were diverse, the vast majority of studies reported significant associations [11,26,31,33,36,40,44,45,50,52,54,56,60,63,64,68,69]. Of the negative studies, one used a threshold-based PRS [59] and another used a PRS including 15 Bonferronisignificant risk SNPs [39] but both excluded APOE entirely.…”
Section: Associations Between Ad Prs Phenotypes and Biomarkersmentioning
confidence: 99%
“…However, in spite of the progress in understanding risk factors related to AD development, the underlying mechanisms involved in this disease have not been completely understood till now, and to date there is no curative treatment for AD [5,6]. Now many genes are proved to significantly influence AD risk, among which the complement component (3b/4b) receptor 1 gene (CR1) has been proved to affect AD susceptibility across different ethnic and districts groups [7][8][9][10][11][12]. Currently, CR1 has been postulated to be a key factor for AD pathogenesis because of its role in regulating complement activity by acting as a receptor of complement C3b protein [13].…”
Section: Introductionmentioning
confidence: 99%